Math, asked by nelsonsana0, 14 hours ago

-11x+(2x/3+3)=5-2(x/3+1)
Answer fast !!​

Answers

Answered by bhanvi116
0

Given: -11x + (\frac{2x}{3} + 3) = 5 - 2(\frac{x}{3} + 1)

To find: Value of x

Solution:

Simplifying the given equation

-11x + \frac{2x}{3} + 3 = 5 - \frac{2x}{3} - 2

Gathering the terms with variable x on L.H.S. and constant terms on R.H.S.

-11x + \frac{2x}{3} + \frac{2x}{3} = 5 - 2 - 3

Taking L.C.M. on L.H.S.

\frac{-33x + 2x + 2x}{3} = 5 - 5

\frac{-29x}{3} = 0

-29x = 0

x = 0, Required solution

Similar questions